2011
DOI: 10.1021/ja203456h
|View full text |Cite
|
Sign up to set email alerts
|

All-Photonic Multifunctional Molecular Logic Device

Abstract: Photochromes are photoswitchable, bistable chromophores which, like transistors, can implement binary logic operations. When several photochromes are combined in one molecule, interactions between them such as energy and electron transfer allow design of simple Boolean logic gates and more complex logic devices with all-photonic inputs and outputs. Selective isomerization of individual photochromes can be achieved using light of different wavelengths, and logic outputs can employ absorption and emission proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
286
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 313 publications
(291 citation statements)
references
References 65 publications
0
286
0
Order By: Relevance
“…Figure 2b shows the equivalent switching circuit of a 1:2 DEMUX, which requires one data input signal and an additional address input to select either output channel to process the input. To date, only several studies associated with a molecular DEMUX have been reported, 11,21,22,[29][30][31] most of which are still based on comprehensive synthetic organic molecules. It is still a great challenge to fabricate a biocompatible DEMUX considering its fundamental and practical significance not only in DNA computing but also in the biomedical field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2b shows the equivalent switching circuit of a 1:2 DEMUX, which requires one data input signal and an additional address input to select either output channel to process the input. To date, only several studies associated with a molecular DEMUX have been reported, 11,21,22,[29][30][31] most of which are still based on comprehensive synthetic organic molecules. It is still a great challenge to fabricate a biocompatible DEMUX considering its fundamental and practical significance not only in DNA computing but also in the biomedical field.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, only fluorescence is utilized as the single signal generation mode, bringing convenience to the operation. In previous studies, the developed DC usually involved several types of optical signals as readouts, such as light absorption, emission or transmission, 21,23,24 making the operation complicated and limiting its further development. Secondly, the utilization of a DNA biomaterial here increases the biocompatibility for potential applications in the biomedical field because each state of a 2-to-4 DC corresponds to a combination, determining whether both, either or neither of the analytes considered as inputs exists in an organism or other complex system.…”
Section: Advanced Logic Circuits For Nonarithmetic Information Procesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 We now use pH sensors to lift the field of molecular logic-based computation [8][9][10][11][12][13] to a much higher plane by demonstrating human-level computing by small molecules. Important advances in the level of complexity of molecular logic have been achieved by using chemical species to link gates, [14][15][16][17] by employing multi-component photochromics, 18,19 by using cuvet arrays, 20,21 and by the use of algorithmic pipeting protocols in multiwell plates. 22 We present the first instance of small synthetic molecules performing a major computation that humans do often during each waking hour.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Photochromic switches have been often exploited for these purposes. [12][13][14][15] However, chemically-addressable systems and redox-switchable molecular devices were also used for the demonstration of molecular keypad locks [16][17][18][19] and flip-flops. 20,21 Surprisingly, the exploitation of supramolecular host-guest phenomena for the demonstration of keypad lock functions has no precedence in the literature.…”
mentioning
confidence: 99%